Guiding CBT supervision: how well do manuals and guidelines fulfil their promise?. (25th January 2016) - Milne, Derek L.
Abstract: Written guidance is part of a coherent support system for CBT supervisors, consistent with general developments in evidence-based practice. In theory, training manuals can help by specifying educational procedures and providing support materials so as to foster fidelity, expertise and effectiveness among supervisors. Supervision guidelines can help by offering supervisors the fruits of research and expert consensus. Together with related resources, such written guidance promises to empower professionals and to benefit patients. But progress with written guidance is very limited within clinical supervision, particularly in controlled research. In marked contrast, locally developed guidance appears to have been implemented successfully within pragmatic studies, a marked achievement when also contrasted with the general healthcare literature. Using eight criteria, the available supervision research is reviewed and conclusions drawn on developing written guidance so as to better fulfil its promise.